Pelatihan Branding Produk pada UKM Ikan Asin - Hapsari Shinta Citra Puspita Dewi; Panji Bana; Muchamad Arif Al Ardha (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Partnership Program (PKM) aims to improve the capacity of salted fish SME actors in strengthening product branding through training, mentoring, and the use of digital media. This activity was designed to address the low level of understanding among business actors regarding brand identity, modern marketing strategies, and the use of digital technology as a means of promotion. Through an interactive training approach tailored to field conditions, participants gained practical understanding of visual identity development, marketing communication, social media use, and marketplace utilization strategies. The results of the PKM showed significant improvements, including an increase in branding understanding from 30% to 85%, visual identity changes by 70% of participants, and a 40% increase in sales within three months. In addition, the use of social media increased from 20% to 75%, followed by an increase in the use of e-commerce as a sales medium. Participants also showed positive responses and high interest in participating in further training. This PKM proves that strengthening branding can increase the competitiveness of SMEs and have an impact on local economic growth. These findings emphasize the importance of continuous training and mentoring support so that SMEs can adapt to market and technological developments.